Improving the National Intellectual Disability Higher Trainee Experience - Abigail Swift (BJPsych Open)
Aims: At several regional representative meetings held by the National Trainee representatives for the Intellectual Disability (ID) faculty within the Royal College of Psychiatrists a number of themes emerged. There were concerns around the ability to disseminate information to new starters as often groups like the Trainee ID whatsapp group are dependent upon word of mouth. Some trainees talked about difficulties meeting particular competencies such as inpatient experience whilst others felt isolated due to small training numbers. There were also changes to the portfolio system that had raised concerns for some.